Simulation of gamma-ray distribution in rocks for determining the registration characteristics of measurement unit of horizontal borehole positional control system; Engineering Research Express; Vol. 1, No. 1 - Golodnykh E. V. Evgeny Vadimovich (2019, 2019)
Title screen